Added value of cell-free DNA over clinical and ultrasound information for diagnosing ovarian cancer - Vanderstichele, A; Ceusters, J; Fischerova, D; Testa, A; Froyman, W; Landolfo, C; Moro, F; Baert, T; Busschaert, P; Venken, T; Lambrechts, D; Vermeesch, J R; et al. (Ultrasound in obstetrics & gynecology, 2025)
OBJECTIVE: We previously proposed two cell-free (cf) DNA-based scores (genome-wide Z-score and nucleosome score) as candidate non-invasive biomarkers to further improve the presurgical diagnosis of ovarian malignancy. We aimed to investigate the added value of these cfDNA-based scores in combination with the clinical and ultrasound predictors of the Assessment of Different NEoplasias in the adneXa (ADNEX) model to estimate the risk of ovarian malignancy. METHODS: In this prospective cohort study, 526 patients with an adnexal mass scheduled for surgery were recruited consecutively in three oncology referral centers. All patients underwent a transvaginal ultrasound examination, and adnexal masses were described according to the International Ovarian Tumor Analysis terms and definitions. cfDNA was extracted from preoperative plasma samples and genome-wide Z-scores and nucleosome scores were calculated. Logistic regression models were fitted for ADNEX predictors alone and after inclusion of the cfDNA-based scores. We report likelihood ratios, area under the receiver-operating-characteristics curve (AUC), sensitivity, specificity and net benefit for thresholds between 5% and 40%, to assess the diagnostic performance of the models in discriminating between benign and malignant ovarian masses. RESULTS: The study included 272 benign, 86 borderline, 36 Stage-I invasive, 113 Stage-II-IV invasive, and 19 secondary metastatic tumors. The likelihood ratios for adding the cfDNA-based scores to the ADNEX model were statistically significant (P < 0.001 for ADNEX without CA 125; P = 0.001 for ADNEX including CA 125). The accompanying increases in AUC were 0.013 when the cfDNA biomarkers were added to the ADNEX model without CA 125, and 0.003 when added to the ADNEX model including CA 125. Net benefit, sensitivity and specificity were similar for all models. The increase in net benefit at the recommended 10% threshold estimated risk of malignancy when adding the cfDNA-based scores was 0.0017 and 0.0020, respectively, for the ADNEX model without CA 125 and the ADNEX model with CA 125. According to these results, adding cfDNA markers would require at least 453 patients per additional true-positive test result at the 10% risk threshold. CONCLUSION: Although statistically significant, cfDNA-based biomarker scores have limited clinical utility in addition to established clinical and ultrasound-based ADNEX predictors for discriminating between benign and malignant ovarian masses. © 2025 International Society of Ultrasound in Obstetrics and Gynecology.
Keywords: ovarian cancer; diagnosis; circulating tumor DNA; early detection; liquid biopsies; ADNEX; nucleosome; fragmentomics